Beispiel Nr: 07
$ \text{Gegeben:} ax^{3}+bx^{2}+cx+d=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ \\ \textbf{Gegeben:} \\ -\frac{1}{4}x^3+\frac{2}{3}x^2 =0\\ \\ \textbf{Rechnung:} \\ x^2(-\frac{1}{4}x+\frac{2}{3})=0 \Rightarrow x=0 \quad \vee \quad-\frac{1}{4}x+\frac{2}{3}=0\\ -\frac{1}{4} x+\frac{2}{3} =0 \qquad /-\frac{2}{3} \\ -\frac{1}{4} x= -\frac{2}{3} \qquad /:\left(-\frac{1}{4}\right) \\ x=\displaystyle\frac{-\frac{2}{3}}{-\frac{1}{4}}\\ x=2\frac{2}{3} \\ \underline{x_1=0; \quad2\text{-fache Nullstelle}} \\\underline{x_2=2\frac{2}{3}; \quad1\text{-fache Nullstelle}} \\$